The Relationship between Native Americans and the Chinese: Representation of the Formation of National Identity in the Short Story Sin Po of the 1940s - Agus Sri Danardana; sartika sari; Sri Yono; Rafiqah Yusna Siregar (ELT (English Language Teaching Prima Journal), 2026)
ABSTRACT This study examines the formation of Chinese national identity in short stories published in the Sin Po newspaper during the 1930s and 1940s, arguing that this identity emerges most clearly in the relationship depicted between the Chinese and the indigenous Indonesian population. Using a qualitative sociology-of-literature approach with content analysis, it reads the stories as social documents and interprets them through Castells's typology of identity construction—legitimizing, resistance, and project identity—alongside theories of imagined and diasporic national identity. The analysis identifies three modes of identification: a legitimizing identity imposed by colonial racial classification ("Nji Patmah"); a resistance identity forged through communal solidarity amid institutional neglect ("Bahaja Api"); and a project identity built on a shared destiny with the indigenous population ("Kemaleman di Desa," "Balesan," "Ampir Sadja," "Bapa Koempoel"). Arranged chronologically, these forms compose a trajectory from an identity received from the colonizer toward one projected in fellowship with indigenous Indonesians. Although the characters remain articulated as Chinese, empathy and a sense of shared destiny already constituted the seeds of Indonesian nationality before independence, revealing national identity as a layered, ambivalent, and medium-borne process.